Epitelização de enxertos cutâneos em feridas recentes de coelhos tratados com membrana amniótica canina e/ou laserterapia - Reis Filho, Nazilton de Paula [UNESP] (2015)
Skin grafting is a simple surgical technique and useful to repair wounds, especially those where there is a difficulty to apply primary closure skin or other reconstructive techniques. However, for the graft survival it is necessary that the healthy wound bed and the presence of an exuberant granulation tissue. This study aimed to evaluate the application of amniotic membrane and laser therapy as potential stimulating healing in grafts applied in wounds without granulation tissue. For this, we used 42 rabbits divided into four treatment groups, control group (CG), membrane group (MG), laser group (LG) and membrane and laser group (MLG), submitted to macroscopic and microscopic evaluation. The macroscopic examination was possible to note that the patients of the groups where the amniotic membrane was used in order to stimulate re-epithelialization (MG and MLG) presented evidences associated with severe inflammatory reaction, graft integration failure and consequent necrosis. In LG patients apparently had the best aspect of the graft in the last valuation date. On the microscopic examination, there was intense integration of the graft to the dermis, high reepithelialization level and scarce inflammatory cells in the graft site of LG group patients. The opposite was observed in patients in the MG and MLG groups, where apparently the presence of amniotic membrane seems to have induced very consistent inflammatory response in the region adjacent to the membrane and the graft, evincing that there was a rejection of the membrane. Finally, the collagen formation does not correlated with other factors such as inflammation and necrosis in any of the treatment groups. We can conclude that laser therapy was effective, contributing to the healing process and integration of the graft. Thus, the canine amniotic membrane should not be used for this purpose because it causes intense inflammatory reaction besides to avoid graft nutrition